Exploring the relationship between Big Food corporations and professional sports clubs: a scoping review. Issue 10 (2nd April 2019) - Ireland, Robin; Chambers, Stephanie; Bunn, Christopher
Abstract: Objective: Professional sport occupies a prominent cultural position in societies across the globe and commercial organisations make use of this to promote their products. The present scoping review explores existing academic literature on the relationship between professional sports clubs and food and drink marketing and considers how this relationship may impact upon the public's health. Design: The scoping review searched six databases. Experts were also consulted. Records written in languages other than English were excluded. We also excluded records relating to mega events (e.g. Olympics, Football World Cup) and alcohol marketing, because of the attention already given to these. Setting: Professional sports clubs. Results: We identified 18 166 titles, reviewed 163 abstracts and read twenty-six full texts. We included six papers in the review. Four were from Australia and New Zealand. The Australasian literature focused largely on the marketing of foods and beverages to children and the potential impact on consumption. Single papers from researchers in Turkey and the USA were identified. The Turkish paper analysed shirt sponsorship in football leagues internationally and showed food and beverage (including alcohol) companies were the most common sponsors. The US paper examined a mixed reaction to a football team named after an energy drink. Conclusions: Commercial relationships between professional sports clubs and Big Food corporations have largely eluded scrutiny in much of the world. The current review highlights the lack of public health research on these relationships. Research exploring the interdependent commercial practices of food and drink companies and professional sports clubs is urgently needed.